Raising Arizona [videorecording (DVD)] - Coen, Joel; Coen, Ethan; Cage, Nicolas, 1965-; Hunter, Holly, 1958-; Wilson, Trey; Goodman, John, 1952-; Forsythe, William, 1955-; McDormand, Frances (Twentieth Century Fox Home Entertainment, 2002)
An ex-con and a police officer decide to get married and start a family. To their dismay, they discover that they can neither have nor adopt children. Desperate, they resort to kidnapping one of the newborn quintuplets of the wealthy Arizona family. However, their attempt at living a normal life is complicated by neurotic co-workers, two fugitives, and a mysterious bounty hunter.